APPROACHING THE VALUES OF THE MAJAPAHIT KINGDOM: A STUDY OF GANESHA STATUES IN TROWULAN MUSEUM - Zahra Pramatatya Soenarko; Izzaditya Dharmaputra Mikail; Rindrah Kartiningsih; Happy Julia Rahmadianti; Rommel Utungga Pasopati (Jurnal Citra Multidisiplin, 2026)
This study addresses the tendency to interpret Majapahit artifacts through fixed symbolic meanings without examining how value is constructed through social experience. The research focuses on the Ganesha statue in Trowulan Museum as a cultural artifact situated within a specific historical context. A qualitative interpretive design is employed, using literature-based analysis and symbolic examination guided by the framework of John Dewey’s theory of value. The findings indicate that the Ganesha statue functions not only as a religious representation but as a medium through which values related to knowledge, authority, and social order are organized. Its symbolic attributes are shown to reflect practical concerns within Majapahit society rather than fixed doctrinal meanings. Comparative analysis reveals that differences between Indian and Majapahit representations result from contextual adaptation rather than variation in form alone. The study also demonstrates that the relocation of the statue into a museum context produces a shift in valuation, where its function changes from ritual practice to educational and cultural interpretation. These findings support the view that value emerges through interaction, use, and changing conditions. The study contributes to cultural and educational research by positioning artifacts as active participants in value formation rather than passive carriers of meaning.